2017
DOI: 10.24263/2304-974x-2017-6-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Qualimetric assessment of diets

Abstract: Keywords:Qualimetry Rating Diet Norm Corresponding author:Oleg Kuzmin E-mail: kuzmin_ovl@ nuft.edu.ua DOI: 10.24263/2304-974X-2017-6-1-7 Introduction. The work's objective is to analyze quality rating of diets from the standpoint of physiological need norms of a person and a daily ration, to further determine the balance of nutrition.Materials and methods. The daily ration of human nutrition (breakfast, lunch, dinner) and the norms of the physiological needs of the average person -to determine the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…-mobile frames; -sticks However, an excessive decrease in temperature also leads to changes in physical and chemical parameters: the reduction of oxidation rates of fatty acids (Warriss P.D., 2000; Kuzmin O. et al, 2017), [15,18]; reduction of the degree of dispersion of fat, which negatively affects the fat holding capacity (FHC), slows down the development of the process of color formation and microbiological parameters: the decrease of the growth of pathogenic microorganisms (James S.J., James C., 2002; Sams A.R., 2001) [16,17]. With a sufficient density of loaves, lowering the temperature can increase the content and break the shell of the sausage during cooking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-mobile frames; -sticks However, an excessive decrease in temperature also leads to changes in physical and chemical parameters: the reduction of oxidation rates of fatty acids (Warriss P.D., 2000; Kuzmin O. et al, 2017), [15,18]; reduction of the degree of dispersion of fat, which negatively affects the fat holding capacity (FHC), slows down the development of the process of color formation and microbiological parameters: the decrease of the growth of pathogenic microorganisms (James S.J., James C., 2002; Sams A.R., 2001) [16,17]. With a sufficient density of loaves, lowering the temperature can increase the content and break the shell of the sausage during cooking.…”
Section: Resultsmentioning
confidence: 99%
“…For producing of highquality products manufacture should use all possible measures (Kuzmin O. et al, 2016Pasichnyi V.M. et al, 2015) [21,18,19,20]. One of such measures is to improve the quality of the production of the most widespread group of sausage products -boiled sausages, which, due to its range and high taste and consumer properties has high demand among the population.…”
Section: Introductionmentioning
confidence: 99%
“…This will provide an alkaline orientation of the population's nutrition. Studies of the structure of nutrition [1] have shown a significant reduction in protein intake, and the body's need for energy is met by increasing the consumption of carbohydrates and fats. Therefore, it is important to increase the number of foods with high biological value, the recipes of which would be based on the provisions of the theory of balanced nutrition, as well as would take into account the economic potential of the consumer [2].…”
Section: Introductionmentioning
confidence: 99%
“…oleptic characteristics (Kanter et al, 2003a), which allows institutions to focus their efforts on shaping the quality of restaurant products (Kuzmin et al, 2017). This is possible due to innovative technologies, using modern methodologies, the latest mathematical apparatus (Dorokhovych et al, 2016).…”
mentioning
confidence: 99%